(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
The translation of culturally-bound musical terms presents significant challenges due to deep differences in linguistic, cultural, and philosophical worldviews. This study explores the difficulties encountered when translating Uzbek musical terminology, particularly terms related to the Shashmaqom tradition, into English. Drawing on the concepts of cultural untranslatability and dynamic equivalence, the research analyzes a corpus of 60 key Shashmaqom terms, including modal systems, rhythmic patterns, vocal techniques, instrument names, and performance styles. The findings reveal that many Uzbek musical terms, such as maqom, shobe, gushe, nasr, soz, hofiz, and tanbur carry rich cultural, spiritual, and historical connotations that lack direct equivalents in English. While English musical terminology tends to be primarily technical and structurally oriented, Shashmaqom terms are deeply embedded in Sufi philosophy, Persian-Arabic literary tradition, and Central Asian cultural identity. The study identifies four major types of translation challenges: lexical gaps, semantic asymmetry, cultural loss, and pragmatic differences. The paper argues that successful translation of such terms requires not only linguistic competence but also profound cultural and ethnomusicological knowledge. It proposes a combined translation approach involving explanatory translation, cultural annotation, and strategic use of domestication and foreignization techniques. The results contribute to the fields of cultural translation studies, ethnomusicology, and Uzbek-English contrastive linguistics.